Prevalence of Carbapenem-Resistant Gram-Negative Clinical Isolates and its Antibiotic Susceptibility Patterns - Bhattarai, Aashis; Dhakal, Prakash; Dhungana, Savita (Journal of Physical and Life Sciences, 2024)
Carbapenem-resistant Gram-negative pathogens are recognized as a major health concern. However little information is available in Nepal regarding carbapenem-resistant Gram-negative bacteria. Therefore, a cross-sectional study was carried out at a tertiary care hospital to examine the prevalence of carbapenemase, metallo-beta-lactamases, and AmPC-beta-lactamases producing organisms in carbapenem-resistant Gram-negative bacteria. A total of 82 Gram-negative bacteria were identified from 825 clinical specimens based on colony characters, Gram staining catalase test, oxidase test, and other biochemical tests. Antibiotic susceptibility testing was performed according to clinical standard institute (CLSI) guidelines 2014. of 82 isolates, 24 (29.3%) were carbapenem-resistant. Of these 33.4% were E. coli, 25% were Pseudomonas, 25% were Klebsiella pneumoniae and 16.7% were Acinetobacter spp. A total of 13 (54.2%) were MBL producers. All MBL producers were multi-drug resistant (MDR). Single isolate of K. pneumoniae was KPC positive. Out of 24 carbapenem-resistant isolates, 20.8% isolates were positive for the AmpC beta-lactamases test. All AmpC beta-lactamases and single isolates of KPC producers were MDR. Among the total of 82 Gram-negative bacterial isolates, 48.8% were MDR organisms. Based on in-vitro testing polymyxin B was found effective against all isolates. Although, MBL and other beta-lactamase producers were not higher than that found in other studies from Nepal, beta-lactamases and MDR organisms should be detected in the hospital setting to prevent the spread of these organisms.